PEMANFAATAN ABU TERBANG BATUBARA UNTUK MENINGKATKAN KETERSEDIAAN P, SERTA PENGARUHNYA TERHADAP PERTUMBUHAN TANAMAN KANGKUNG DARAT (Ipomoea reptans Poir) - Panggah Jayengswasono; Karuniawan Sigit Wicaksono (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
Cultivation in sandy soils encounters many obstacles due to the nature of the soil, which has a poor ability to hold water and nutrients. In order to increase plant yield, it is necessary to add soil amendments that can improve the properties of sandy soil. The purpose of this study was to elucidate the impact of giving coal fly ash as a soil amendment on the chemical properties of soil and plants, as well as plant growth and production. The study was conducted in a greenhouse with different doses of coal fly ash applied to the growing media. The results showed that the higher dose of coal fly ash could increase the total P content (210-310%), P-available (127%), and soil Pb content (28%) compared to the control. Meanwhile, the high dose of coal fly ash can harm the growth and production of water spinach.